A Review of the Properties and Applications of Ozone in Endodontics: An Update - Mohammadi, Zahed; Shalavi, Sousan; Soltani, Mohammad Karim; Asgary, Saeed (Iranian Endodontic Journal, 2013)
Ozone is a triatomic molecule consisting of three oxygen atoms. It is applied to oral tissues in the forms of ozonated water, ozonated olive oil and oxygen/ozone gas. This paper presents a brief review on the chemistry of ozone as well as its medical and dental applications focusing on its use in endodontics. Ozone’s antimicrobial activity, its effect on dentin bonding, toxicity and contra-indications are also reviewed.